2D Forward Looking SONAR in Underwater Navigation Aiding: an AUKF-based strategy for AUVs. Issue 2 (2020) - Franchi, Matteo; Ridolfi, Alessandro; Zacchini, Leonardo
Abstract: This paper proposes an underwater navigation system where linear speed estimations, obtained with a 2D Forward-Looking SONAR (FLS), are integrated within a navigation filter and this solution is shown to work satisfyingly in the absence of Doppler Velocity Log (DVL) readings. Both to provide a better description of the system, which is a dynamic entity in a dynamic environment and to characterize FLS measurements, an Adaptive Unscented Kalman Filter (AUKF)-based estimator is here proposed. The solution has been tested and validated offline making use of navigation data obtained during sea trials performed in July 2018 with FeelHippo AUV at the basin of the NATO Science and Technology Organization Centre for Maritime Research and Experimentation (CMRE), La Spezia (Italy).